2023
DOI: 10.3389/fvets.2023.1148766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carnosine on the embryonic development and TiO2 nanoparticles-induced oxidative stress on Zebrafish

Abstract: Oxidative stress is due to an unbalance between pro-oxidants, such as reactive oxygen (ROS) and nitrogen (RNS) species, and antioxidants/antioxidant system. Under physiological conditions these species are involved in different cellular processes such as cellular homeostasis and immune response, while an excessive production of ROS/RNS has been linked to the development of various diseases such as cancer, diabetes, and Alzheimer's disease. In this context, the naturally occurring dipeptide carnosine has shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…[117][118][119][120] In addition to behavioral impairments, TiO 2 NPs exposure causes oxidative stress, promotes neuronal proliferation, decreases motor neuron axon length, alters gene expression, and increases cell apoptosis. [120][121][122][123] Two study chose the adult stage of zebrafish for TiO 2 NPs exposure, and their results suggested that TiO 2 NPs exposure caused cognitive deficit, promoted neuroinflammation, and altered biochemical constituents of the brain. 124,125…”
Section: Neurotoxic Effects Of Tio 2 Nps In Zebrafishmentioning
confidence: 99%
“…[117][118][119][120] In addition to behavioral impairments, TiO 2 NPs exposure causes oxidative stress, promotes neuronal proliferation, decreases motor neuron axon length, alters gene expression, and increases cell apoptosis. [120][121][122][123] Two study chose the adult stage of zebrafish for TiO 2 NPs exposure, and their results suggested that TiO 2 NPs exposure caused cognitive deficit, promoted neuroinflammation, and altered biochemical constituents of the brain. 124,125…”
Section: Neurotoxic Effects Of Tio 2 Nps In Zebrafishmentioning
confidence: 99%
“…31,32 For example, chaperone abundance may change when cells encounter UCNPs or other nanomaterials. 28,30,33 The cellular uptake of UCNPs is generally mediated by membrane-delimited compartments. 11 Therefore, chaperones relevant to membrane or vesicle trafficking, such as Grp78 and Grp94, are sensitive indicators of NP-induced stress.…”
Section: Introductionmentioning
confidence: 99%
“…In sunscreen products, TiO 2 is used as a UV filter to protect the skin from harmful UV rays when exposed to sunlight [ 25 ]. The ecotoxicological impact of TiO 2 NPs has been noticed in different organisms, such as Daphnia magna [ 26 ], Mytilus galloprovincialis [ 27 , 28 ], Artemia salina [ 29 ], Crassostrea gigas [ 30 ], Paracentrotus lividus [ 31 ], and Danio rerio [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%